2014
DOI: 10.1155/2014/298352
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Haemoplasma Infections in Stray Cats in Northern Italy

Abstract: This study investigated the prevalence of feline haemoplasma infections in a number of stray cat colonies in Milan, Northern Italy. Blood samples from 260 stray cats were evaluated, with conventional PCR, for the presence of DNA associated with Mycoplasma haemofelis (Mhf) and “Candidatus Mycoplasma haemominutum” (CMhm). Odd ratios (OR) were calculated to identify risk factors for haemoplasma infections. PCR was positive in 86 out of 260 subjects (33.1%), with a prevalence of 10.8% (28/260 cats) for Mhf and 22.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
25
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 29 publications
13
25
4
3
Order By: Relevance
“…The individual CMhm and CMt prevalences were similar to previous Brazilian studies Macieira et al, 2008;Miceli et al, 2013;Santis et al, 2014;Santos et al, 2009), however the Mhf prevalence was higher than those previously reported in RS , MA and MT (Miceli et al, 2013). As would be expected, the individual prevalence figures found in our study were lower than those in international studies where only cats attending veterinary practitioners (Jenkins et al, 2013;Lobetti and Lappin, 2012;Spada et al, 2014;Sykes et al, 2007) or cats with a clinical suspicion of haemoplasmosis (Jenkins et al, 2013;Lobetti and Lappin, 2012;Spada et al, 2014;Sykes et al, 2007) were sampled; but higher than those found in clinically normal cats used as blood donors (Hackett et al, 2006). These differences in prevalence may reflect variations in the groups of cats studied and the risk factors for haemoplasma infection.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The individual CMhm and CMt prevalences were similar to previous Brazilian studies Macieira et al, 2008;Miceli et al, 2013;Santis et al, 2014;Santos et al, 2009), however the Mhf prevalence was higher than those previously reported in RS , MA and MT (Miceli et al, 2013). As would be expected, the individual prevalence figures found in our study were lower than those in international studies where only cats attending veterinary practitioners (Jenkins et al, 2013;Lobetti and Lappin, 2012;Spada et al, 2014;Sykes et al, 2007) or cats with a clinical suspicion of haemoplasmosis (Jenkins et al, 2013;Lobetti and Lappin, 2012;Spada et al, 2014;Sykes et al, 2007) were sampled; but higher than those found in clinically normal cats used as blood donors (Hackett et al, 2006). These differences in prevalence may reflect variations in the groups of cats studied and the risk factors for haemoplasma infection.…”
Section: Discussionsupporting
confidence: 87%
“…The overall haemoplasma prevalence was similar to those reported in the Brazilian states of RJ (Macieira et al, 2008), MA , SP (de Bortoli et al, 2012), MT (Miceli et al, 2013) and in studies from UK (Tasker et al, 2003a) and Italy (Gentilini et al, 2009), however studies conducted in stray cats from other Brazilian states Santis et al, 2014;Santos et al, 2009), Portugal (Martínez-Díaz et al, 2013 and Italy (Spada et al, 2014) reported higher overall prevalences. The individual CMhm and CMt prevalences were similar to previous Brazilian studies Macieira et al, 2008;Miceli et al, 2013;Santis et al, 2014;Santos et al, 2009), however the Mhf prevalence was higher than those previously reported in RS , MA and MT (Miceli et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations